도시재생사업에 대한 주민만족도 결정요인 연구 - 도시활력증진사업을 중심으로 - 서남진(Suh, Nam Jin); 김호철(Kim, Ho Cheol) (대한부동산학회지, 2019)
이 연구는 도시재생사업의 주민만족도에 영향을 미치는 요인들에 대해 전문가와 지역주민 설문조사를 통해 요인의 상대적 중요도 및 주민만족과의 인과관계 등을 알아보았다. 실증분석 결과 전문가와 지역주민 모두가 물리․환경적 개선이 주민만족을 위해 가장 중요하다고 생각하는 것으로 나타났다. 도시재생이 도시쇠퇴 문제 해결을 위한 물리적, 경제적, 사회적, 환경적 측면을 망라한 통합적인 접근이라고 하지만 여전히 물리환경적인 부분이 중요함을 보여주었다. 세부적으로는 물리 환경적 요인 중에서는 기반시설 확충과 가로(보행)환경 정비 등 공공의 이익과 관련되는 부분은 상대적 중요도가 높고 사업 이후의 주민 인식도 긍정적인 것으로 나타났다. 경제적 측면에서는 지역맞춤형 사업 발굴, 유동인구 증가 등이, 그리고 사회적 측면에서는 주민참여 확대, 지원·협업 체계 강화가 주민만족을 위해 중요한 요인으로 나타났다. 상업지역내 도시활력증진사업의 만족도가 주거지역보다 현저히 떨어짐을 감안, 향후 상업지역 도시재생사업에는 사업 착수 전 지자체, 주민, 단체, 전문가가 참여하는 네트워크를 통해 사전에 충분한 협의와 철저한 계획수립 및 점검이 필요한 것으로 나타났다. This empirical analysis shows that physical and environmental improvements are the most important for residents' satisfaction. Although urban regeneration is an integrated approach that encompasses physical, economic, social, and environmental aspects to solve the problem of urban decline, it still demonstrated the importance of physical and environmental parts. In detail, among the physical and environmental factors, factors related to public interests such as infrastructure expansion and street (walking) environment readjustment were found to be relatively important and to be accepted positively in after-project recognition. From an economic perspective, search for regionally customized projects and increase of floating population, and from a social perspective, the expansion of residents' participation and enhancement of support and cooperation systems were important factors for residents' satisfaction. Considering that satisfaction level of urban revitalization projects in commercial areas is significantly lower than that of residential areas, it has been shown that commercial urban regeneration projects in future require sufficient consultation in advance and thorough planning and inspection through networks involving local governments, residents, regional organizations, and experts before the start of the project. KCI Citation Count: 0